On the integral of a function along the trajectories of a nilpotent flow - Parasyuk, I. O.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish conditions under which the integral of a function along a nilpotent flow on the Heisenberg-Iwasawa manifold increases not faster than $|t|^{1/2+ ε},\; 0 < ε < 1$ and indicate cases where this integral can be represented as a superposition of a function defined on a nilmanifold and a nilpotent flow.